2009
DOI: 10.1111/j.1365-2699.2009.02157.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic analyses suggest that a deciduous species (Ostryopsis davidiana Decne., Betulaceae) survived in northern China during the Last Glacial Maximum

Abstract: Aim  Palaeontologial data suggest that all temperate forest species in northern China migrated southwards during the Last Glacial Maximum (LGM) and recolonized post‐glacially within the Holocene. We tested this assumption using phylogeographical studies of a temperate deciduous shrub species (Ostryopsis davidiana Decne., Betulaceae), which has a wide distribution in northern China. Location  Northern China. Methods  We sequenced two chloroplast DNA (cpDNA) fragments (trnL–trnF and psbA–trnH, together about 130… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 42 publications
7
101
1
Order By: Relevance
“…Phylogeographic Structure and Inference of Demographic Patterns -Our results on the phylogeographic structure of R. dauricum were consistent with previous studies of temperate montane flora in northeastern China, which were strongly structured phylogeographically (Chen et al 2008;Tian et al 2009;Chen et al 2012b). In this study, N ST was significantly …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Phylogeographic Structure and Inference of Demographic Patterns -Our results on the phylogeographic structure of R. dauricum were consistent with previous studies of temperate montane flora in northeastern China, which were strongly structured phylogeographically (Chen et al 2008;Tian et al 2009;Chen et al 2012b). In this study, N ST was significantly …”
Section: Discussionsupporting
confidence: 81%
“…Similar phenomena have also been observed in Ostryopsis davidiana Decne. (Tian et al 2009), Fagus engleriana Seemen ex Diels (Lei et al 2012), Quercus variabilis Blume (Chen et al 2012a) and Juglans cathayensis Dode (Bai et al 2014). In addition, the results of the neutrality test suggested stable population dynamics recently, implying no spatial expansions in the post-glaciations.…”
Section: ]mentioning
confidence: 99%
“…Initially, temperate forests in the Northern Hemisphere were thought to have retreated southward during the glacial periods and then to have re-colonized the previously uninhabitable northern regions at the warm and wet interglacials (Hewitt, 2000(Hewitt, , 2004. However, recent phylogeographic studies of cool-temperate trees in continental East Asia have clearly shown that this southern refuge model does not apply: cool-temperate trees survived the ice ages in situ rather than moved to the south (Bai et al, 2010;Hu et al, 2008;Liu et al, 2014;Tian et al, 2009;Zeng et al, 2011;Zeng et al, 2015). Consequently, postglacial range expansions of the eastern Asian temperate trees were necessarily spatially limited compared to the southern refuge model.…”
Section: Introductionmentioning
confidence: 95%
“…If this is correct, then the current distribution of populations is likely to have resulted from expansions from these different refugia, with secondary contact occurring in some areas giving rise to populations (for example, populations 2, 11, 23 and 24) polymorphic for mitotypes diagnostic of the different phylogeographic groups. Other surveys of molecular variation in different plant species occurring in central China, such as Taxus wallichiana (Gao et al, 2007), Pinus tabulaeformis (Chen et al, 2008), Ostryopsis davidiana (Tian et al, 2009), Eurycorymbus cavaleriei , have also indicated that multiple refugia existed in this region during the Quaternary.…”
Section: Biogeographic Historymentioning
confidence: 99%
“…These two species occur exclusively in central China where many indigenous species shifted their distribution ranges in response to Quaternary climatic oscillations even though the region was never covered by ice sheets during the Quaternary (Chen et al, 2008;Tian et al, 2009). The occurrence of range fragmentation and adaptation to new niches during this period may have promoted speciation in the region (Qian and Ricklefs, 2000).…”
Section: Introductionmentioning
confidence: 99%